Variation in Foliage Yield and Yield Component Traits and Preference for Leaf Quality Traits in Amaranthus Cruentus [L.] Genotypes - Adeniji, O. T.; Badmus, A.A.; Sabo, E.; Peter, J.M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
Amaranthus cruentus is a traditional leaf vegetable in Nigeria. At present, there are few commercial varieties. Development of new varieties requires systematic assessment of foliage yield and yield contributing traits. The objectives of this study are to evaluate variation for foliage yield and yield traits, determine the influence of time of harvest (4 or 5 weeks after sowing) on foliage yield, and assess preference for genotypes, leaf yield and leaf quality traits. Nine Amaranthus cruentus genotypes were grown in a randomized complete blocks design with three replications. Sunken beds were made at 1 m x 2 m, each bed was separated by alley of 1m. A total of 16 beds constituted a replicate, 8 beds were allotted to harvest at 4 weeks, another 8 beds to harvest at 5 weeks. Each bed was treated with 4 Kg of matured farmyard manure. Combined analysis of variance was performed on mean data. Participatory selection was conducted to identify preferred genotypes and horticultural traits. Genotypes were similar or dissimilar for foliage yield and yield component traits at 4 and 5 weeks harvest. Genotype by Year Interaction revealed statistically significant mean squares at 4 and 5 weeks harvest for some traits. Considering multiple traits at 4 weeks harvest, AM 25 and AM 45 performed best for leaves/plant and leaf dry weight, while AM 42 is promising for leaf yield, leaf length and leaf width. At 5 weeks harvest, AM 45 performed best for leaf yield, leaf fresh weight and dry weight. AM 25, AM 42, AM 45 and AMLOC are capable of developing rapidly and producing large quantities of biomass under short cycle harvest.